Fermentasi Jali Menggunakan Bakteri Selulolitik dan Bakteri Asam Laktat untuk Pembuatan Tepung - Handayani, Rini (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTJali (Coix lacryma-jobi L.) is a cereal plant. Jali has a high nutritional content. The protein content of jali is greater than sorghum, which is 11 g / 100 g and a high calcium content of 213 mg / 100 g. Cereal fermentation uses two types of microbes; lactic acid bacteria and cellulolytic bacteria. Selection of the best lactic acid bacteria and cellulolytic bacteria with clear zone testing. Isolates in the clear-zone test were isolates of lactic acid bacteria 478, 504, 508, 520, 525, 540, 543, 546, 548 and cellulolytic bacteria isolates A6, A11, A12. Clear cut test results obtained the best isolates 478 and A11 which are used as fermented cereal jelly inoculum. Jali cereals were fermented with four treatments: control, addition of BAL inoculum, addition of cellulolytic bacterial inoculum and addition of BAL mixed inocula and cellulolytic bacteria. Jali cereal fermentation was carried out for two days and sampling was performed to determine the activity of bacterial growth during fermentation, pH and temperature. The fermented Jali cereal is then dried and made flour. Proximate analysis was performed on Jali flour. The results showed that the addition of bacterial cellulolytic inoculum had a higher protein content of 11.64% compared to other treatments, BAL 7, 43%, BAL + BS 6.26% and 5.08% control. Microscopic analysis was performed to determine the effect of fermentation on starch granules. The use of bacterial inoculum in the manufacture of Jali fermented flour can improve the quality and quantity of nutrient content.Keywords: lactic acid bacteria, cellulolytic bacteria, fermentation, Jali cereals.